Effects of Induced Endotoxaemia on Global Cardiovascular, Oxygenation and Haematologic Variables and the Integrity of the Endothelial Glycocalyx in the Horse - Stephan Neudeck; Philipp K. Sauter; Annette P. N. Kutter; Barbara Steblaj; Franz J. Söbbeler; Julia Reiners; Fritjof Freise; Alvaro. J. Gutiérrez Bautitsta; Sabine B. R. Kästner (Veterinary Medicine and Science, 2025)
ABSTRACT Background Endotoxaemia is a significant cause of morbidity and mortality in equids due to perfusion impairment and possible destruction of the glycocalyx. Objectives To evaluate our hypothesis that endotoxaemia induces changes in global cardiovascular and haematologic parameters and compromises glycocalyx integrity, evidenced by an early rise in plasma shedding products. Study design In vivo experiments Methods In a prospective, randomised, controlled experimental trial, endotoxaemia was induced with E. coli B55:O5 LPS 30 ng kg−1 over 30 min IV in six healthy adult horses ventilated with oxygen supplemented with isoflurane. Standard cardiovascular variables were recorded and calculated, and leucocyte counts, lactate, heparan sulphate and syndecan‐1 concentration were determined at baseline (B) before endotoxin and at 0, 30, 60 and 120 min after endotoxin. Data were analysed using mixed models and adjusted by Tukey‐Kramer (SAS Enterprise Guide Software 7.1). Results After endotoxin (120 min), a significant increase (p ≤ 0.05) in cardiac index (43 ± 9 vs. 80 ± 15 mL kg−1 min−1, p < 0.01), in oxygen delivery index (8 ± 3 vs. 17 ± 4 mL min−1 kg−1, p <0.001), in pulse pressure variation (8 ± 3 vs. 17 ± 4, p < 0.01) and in lactate (1.55 ± 0,9 vs. 4.4 ± 0.52 mmol L−1, p < 0.0001) occurred with a decrease in systemic vascular resistance index (247 ± 87 vs. 83 ± 20 dynes s kg cm−5, p < 0.001), diastolic arterial blood pressure (69 ± 14 vs. 38 ± 5 mmHg; p < 0.001), and leucocyte counts (5.6 ± 1.3 vs. 1.5 ± 0.3 G l−1, p < 0.0001). No changes in the glycocalyx degradation products could be found. Conclusion Short‐term experimental endotoxaemia under isoflurane induced anticipated cardiovascular changes but did not alter glycocalyx shedding products in this study.